DEVELOPMENT OF AIR QUALITY AND BRICK KILNS DURING THE ONSET OF COVID-19: AN ANALYSIS - PERVAIZ, S; KHAN, FZ; JAVID, K; ALTAF, A; ASLAM, F; TAHIR, MAA; TALIB, B; ARIF, H; HAYAT, S (Biological and Clinical Sciences Research Journal, 2022)
Coronavirus and air pollution,having a positive correlation, are inauspiciouslythe greatest challenge of the millennium. Therefore, the study presented the initial outcomes from the analysis of the COVID-19 impact on (1) air qualityand, (2)informal sector i.e. old technology brick kiln industry. In order to evaluate the progress, the spatial analysis was carried out,comprising aerosol optical depth, sulfur dioxide, carbon monoxide, carbon dioxide and ozone with the inclusion of metrological element i.e. rainfall and environmental index (NDVI). The results of the spatial data indicated that the air quality of Punjab improved with the lockdown policy. However, improvements vary across the districts and were absent in a few districts where no strict lockdown policy was observed. During lock-down,fluctuation in rainfall and decrease in NDVI,which had no positive impact in reducing the pollutants concentration in the atmosphere, was observed. The spatial correlation results presented that the pandemic lock-down helped in the reduction of the extent of air pollution. In addition, in the COVID-19 anthropause, Government of the Punjab initiated a stringent action to ban outdated brick kilns causing air pollution. Resultant, conversion of old technology brick kilns into Zig-Zag Technology is a remarkable step to mitigate smog.